An enigmatic Holocene podocopid ostracod from a submarine cave, Okinawa, Japan: 'living fossil' or adaptive morphotype?. (2nd August 2016) - Chiu, Wing-Tung Ruby; Yasuhara, Moriaki; Iwatani, Hokuto; Kitamura, Akihisa; Fujita, Kazuhiko
Abstract : Submarine cave faunas remain poorly understood, and only a few stygobite podocopid ostracods are known. We describe an enigmatic submarine cave ostracod, Tabukicypris decoris gen. et sp. nov., from Holocene sediment cores taken from the Daidokutsu submarine cave off Ie Island, Okinawa, Japan. This species is endemic to the submarine cave environment. At least part of its enigmatic morphology, especially the distinct pore clusters in the anterior and posterior parts, is probably an adaptation to the submarine cave environment. There is no clear morphological evidence to indicate that Tabukicypris decoris is a 'living fossil'. The morphological characters of this stygobite indicate three possible origins of this species: from a deep-sea, interstitial or tropical open shallow-marine environment. http://zoobank.org/urn:lsid:zoobank.org:pub:25E37E49-C0A0-4A49-A8D8-E4AE9D85DB74